2018
DOI: 10.18805/ijar.b-816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-weaning probiotic treatments on growth performance and biochemical blood parameters of Holstein calves

Abstract: The present study was conducted to assess the effects of pre-weaning probiotic treatments on growth performance of male Holstein calves. For experimental treatments, 20 male calves were divided into 2 groups as of control and treatment group. Control group calves were supplied with fresh milk daily in two meals without any growth promoting supplement. Together with fresh milk supply, treatment group calves were supplied with additional 2 g probiotics to their morning meal. Throughout 56-day milk-feeding period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…The use of “Stimix Zoostim” and “Normosil” probiotics helped in the reduction of feed consumption per 1 kg of body weight gain. The data we have obtained are consistent with the results of the study conducted by Ülger [ 28 ], who found that calves receiving probiotics consumed 2% more feed than the calves from the control group. The feed conversion rate was 9.52% better than that of the control group (p<0.05).…”
Section: Discussionsupporting
confidence: 91%
“…The use of “Stimix Zoostim” and “Normosil” probiotics helped in the reduction of feed consumption per 1 kg of body weight gain. The data we have obtained are consistent with the results of the study conducted by Ülger [ 28 ], who found that calves receiving probiotics consumed 2% more feed than the calves from the control group. The feed conversion rate was 9.52% better than that of the control group (p<0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Kocyigit et al (2015) also stated that feed efficiency ratio of the female dairy calves in 10 g head/day DFM plus EFE group was 1.7 times better than that of calves in control group. Parallel findings were also reported by Jenny et al (1991), Hamza et al (1996, Gorgulu et al (2003), Isık et al (2004) and Ulger (2019), and they indicated respectively 25.1%, 25.5%, 15.2%, 11.1%, 10.5% better feed efficiency ratios of the calves in DFM group compared to control group. As the feed efficiency ratios of the male calves in different DFM plus EFE levels during from birth to 6 months of age were compared to each other, it was 2.9% better in favor of the calves in 10 g head/day DFM plus EFE group.…”
Section: Resultssupporting
confidence: 83%
“…In the present study, weaning weight of the male calves in 10 g head/day of DFM plus EFE group were 7.3% heavier than these of animals in control group. Similarly, studies carried out by Jatkauskas & Vrotniakiene (2010) and Ulger (2019) reported that the weaning weights of the calves in DFM group were 9.4% and 5.2% respectively higher than these of calves in control group.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations